The future of Murmansk Oblast assessed by three Delphi panels - Yrjö Myllylä (Geographical Society of Finland, 2006)
This paper evaluates the development of the socio-spatial structures and geoeconomic position of Murmansk Oblast up the year 2025. The study applies strong prospective trends and industrial cluster approaches in analysis and interpretation and it interprets the results in the context of regional development theories. The Delphi method is applied for analysing the potential development paths of Murmansk Oblast. Two Delphi panels were set up in 2005. The panel data in this article consist of the answers of 77 persons including pilot interview. The experts in the Murmansk panel are from Murmansk Oblast, the ones in the Moscow panel are from Moscow and St. Petersburg, and those in the international panel come from Finland, Norway and Great Britain. The clusters of transportation and energy will be the most probable growth sectors in Murmansk Oblast during 2005–25. According to the expert panels the three most important strong prospective main trends influencing socio-economic development in Murmansk Oblast constitute the potential of logistics and transport, the impacts of new technology and globalisation. From the viewpoint of development theories the development of Murmansk Oblast seems to rely very much on the argumentation of the resources and physical environment and supply-side theories.